2016
DOI: 10.1891/0730-0832.35.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude-Integrated Electroencephalography Interpretation During Therapeutic Hypothermia: An Educational Program and Novel Teaching Tool

Abstract: Therapeutic hypothermia (TH) is now considered a standard in tertiary NICUs. Amplitude-integrated electroencephalography (aEEG) is an important adjunct to this therapy and is gaining acceptance for use on the neonatal population. It can be easily incorporated into practice with appropriate education and training. Current publications are lacking regarding nursing care of neonatal patients undergoing th with the use of aEEG. This article presents a broad educational program as well as novel teaching tool for ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
1
0
2
Order By: Relevance
“…Na segunda fase da EHI, há o acúmulo de neurotransmissores excitatórios e apoptose celular. Se a segunda fase iniciar, qualquer lesão cerebral é consideradairreversível 3,4 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Na segunda fase da EHI, há o acúmulo de neurotransmissores excitatórios e apoptose celular. Se a segunda fase iniciar, qualquer lesão cerebral é consideradairreversível 3,4 .…”
Section: Introductionunclassified
“…A HT é uma técnica utilizada para neuroproteção, mediante mecanismos de diminuição do metabolismo cerebral, redução do edema cerebral citotóxico, da pressão intracraniana e inibição da apoptose celular. Consiste em submeter o RN a termo ou pré-termo tardio (a partir de 36 semanas) a uma temperatura de 33,5 o C dentro das 6 primeiras horas de vida e, durante 72 horas de resfriamento, reaquecer o mesmo de forma lenta e progressiva 3,4 .…”
Section: Introductionunclassified
“…Currently, the latest treatment methods for HE in preterm infants, such as mild hypothermia therapy, are recommended to be conducted as early as possible because early diagnosis and prognostic prediction can provide evidence for its early treatment. In the past, however, the early diagnosis of HE in preterm infants mainly depended on previous onset, clinical manifestations, and MRI images, which lagged in time and delayed the diagnosis, resulting in missing the best time for treatment [1]. Multiple studies globally have concluded that it is difficult to assess prognosis and take measures for neurological protection based on previous onset, clinical manifestations, and MRI imaging and other early diagnostic techniques, as well as the severity of the disease, because the best therapeutic range of HE in preterm infants is approximately 6 h [2,3].…”
Section: Introductionmentioning
confidence: 99%